Radiation-Induced Lung Injury and Inflammation in Mice: Role of Inducible Nitric Oxide Synthase and Surfactant Protein D - Malaviya, Rama (Toxicol Sci, 2015)
Reactive nitrogen species (RNS) generated after exposure to radiation have been implicated in lung injury. Surfactant protein D (SP-D) is a pulmonary collectin that suppresses inducible nitric oxide synthase (iNOS)-mediated RNS production. Herein, we analyzed the role of iNOS and SP-D in radiation-induced lung injury. Exposure of wild-type (WT) mice to γ-radiation (8 Gy) caused acute lung injury and inflammation, as measured by increases in bronchoalveolar lavage (BAL) protein and cell content at 24 h. Radiation also caused alterations in SP-D structure at 24 h and 4 weeks post exposure. These responses were blunted in iNOS(−/−) mice. Conversely, loss of iNOS had no effect on radiation-induced expression of phospho-H2A.X or tumor necrosis factor (TNF)-α. Additionally, at 24 h post radiation, cyclooxygenase expression and BAL lipocalin-2 levels were increased in iNOS(−/−) mice, and heme oxygenase (HO)-1(+) and Ym1(+) macrophages were evident. Loss of SP-D resulted in increased numbers of enlarged HO-1(+) macrophages in the lung following radiation, along with upregulation of TNF-α, CCL2, and CXCL2, whereas expression of phospho-H2A.X was diminished. To determine if RNS play a role in the altered sensitivity of SP-D(−/−) mice to radiation, iNOS(−/–)/SP-D(–/–) mice were used. Radiation-induced injury, oxidative stress, and tissue repair were generally similar in iNOS(–/–)/SP-D(–/–) and SP-D(–/–) mice. In contrast, TNF-α, CCL2, and CXCL2 expression was attenuated. These data indicate that although iNOS is involved in radiation-induced injury and altered SP-D structure, in the absence of SP-D, it functions to promote proinflammatory signaling. Thus, multiple inflammatory pathways contribute to the pathogenic response to radiation.